RANCANG BANGUN MESIN PENGIRIS DAUN TALAS BENENG - Ridho Bagus Purwansyah; Benny Nainggolan; Febri Sulistiyo; Robert Napitupulu; Adhe Anggry (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Taro Beneng (Xanthosoma undipes) is an abbreviation of large and koneng which means large and yellow which has prospects as an alternative food ingredient other than rice which is included in the type of tubers. This plant thrives in the Bangka Belitung area and has an economical selling value, one of which is taro leaves. Taro leaves can be used as raw material for making tobacco cigarettes. The processing of taro leaves by Mr. Arizal is done by chopping beneng taro leaves using a chopping machine with a thickness of 1.5-2 mm. This is still not in accordance with market demand that wants a thickness of 0.5–0.8mm. This study aims to design and build a taro leaf slicing machine with a thickness of 0.5-0.8 mm with a capacity of 5 Kg/hour. The research method used is using a synthesis system in view of combining design ideas with the stages of clarifying and translating the client's wishes. Then these desires are represented so that they can be brought into the process of designing machines, making choices, analyzing choices and the interrelationships between competing options, assessing the trade-offs in them and evaluating them. Based on the design of the taro beneng leaf slicing machine, the results obtained are the machine is capable of slicing leaves with a thickness of 0.5 - 0.8 millimeters with an average slicing result of 0.75mm. The cutting capacity of the taro leaf slicing machine is 4.8 kg/hour or only 53% which can be sliced ​​from an average of 230 grams in an effective scale.